Islamic Media Bibliometric analysis based on scientific publications in ASEAN countries - Febriani, Fidzri Nur; Maika, Muhammad Ruslianor (Universitas Padjadjaran, 2023)
Islamic media has a role in economic development, as seen from the many institutions in ASEAN countries that conduct research on various forms of Islamic media and make it a nationally and internationally indexed scientific publication. However, researchers have yet to find any study on ASEAN countries' cooperation in searching for scientific works on the theme of Islamic media, which were analyzed using the R-Package software application. Therefore, this study aimed to determine Islamic Media Bibliometric analysis based on scientific publications in ASEAN countries through study the core information, the number of the most relevant authors, the number of countries' scientific production, types of documents, active affiliations, and the conceptual structure of scientific publications in Islamic media in ASEAN countries. This research used the bibliometric analysis method. Data was collected by searching the Scopus database for Islamic media keywords based on articles, titles, and keywords. The study results obtained 280 documents from 2007 to 2021, including articles and conference papers. Malaysia had the highest number of countries' scientific production in Islamic media scientific publications in ASEAN countries, with 228 frequencies. According to the highest number of scientific publications in Islamic media in ASEAN countries, the National University of Malaysia has produced the highest number of active institutions (31 frequencies). In addition, the study results already include core information containing key data, document types, document contents, authors, and author collaborations needed in this study.